Applying the transtheoretical model to adolescent academic performance using a person-centered approach : a latent cluster analysis. - Moreira, Paulo (2022)
According to the transtheoretical model (TTM), intentional behavioral change to improve academic performance at school is a process that involves a progression through five discrete stages: precontemplation, contemplation, preparation, action, and maintenance. The current person-centered study assessed the emotional and sociocognitive characteristics of adolescent students (n = 343) with distinct academic performance stage of change profiles. Latent class analysis revealed five emergent groups. These groups mapped well onto the different academic performance stages of change: (1) students in a precontemplation stage; (2) students transitioning from precontemplation to contemplation; (3) students in a contemplation/preparation stage; (4) students in an action/maintenance stage; and (5) students outside the change process due to strong prior academic performances. In accordance with the TTM, group differences in personality, wellbeing, emotional/behavioral problems, learning approaches, and engagement with school indicated students in the more advanced stages of change had more adaptive psychological resources.